2004
DOI: 10.2320/matertrans.45.2165
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Investigation of Equal Channel Angular Extrusion Process

Abstract: In this study, the effect of material properties on deformation pattern and strain distribution of the commercially-available pure titanium (CP-Ti) specimen during an equal channel angular extrusion (ECAE) was investigated. Finite element analyses were carried out for twodimensional plane strain condition at elevated temperatures. Material properties were assumed by hardening, softening, and no hardening behaviors based on the measured experiment data. The effects of friction conditions, die geometries, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…Kim et al [5] numerically investigated the effect of die geometry and material properties under various processing conditions. Lee et al [6] examined the deformation patterns after multi-pass ECAE in A and C routes using FE analyses in order to explore the effect of processing routes. The shearing patterns predicted by FE simulations were very similar to the results of the previous study [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [5] numerically investigated the effect of die geometry and material properties under various processing conditions. Lee et al [6] examined the deformation patterns after multi-pass ECAE in A and C routes using FE analyses in order to explore the effect of processing routes. The shearing patterns predicted by FE simulations were very similar to the results of the previous study [7].…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees well with FE analysis. 23) 4. Effect of the Process Zone Angle Figure 7 shows the difference of materials flow for the variation of the angle (30, 60 and 90 ), with GR and without GR models.…”
Section: Sph Analysis Of Ecap Process By Using Grain Refinement Model 23mentioning
confidence: 99%
“…It was found from one study that the deformation within the workpiece was inhomogeneous unlike the ideal shear deformation and a lesser shear that occurred in the outer part of the workpiece [10]. Deformation patterns for the multi-pass ECAP in routes A and C were investigated under a plane strain condition in order to explore the effect of processing routes [11]. The shearing patterns predicted by FE simulations in these studies were very similar to the experimental results of the previous study reported by Furukawa et al [3].…”
Section: Introductionmentioning
confidence: 99%